Viable but nonculturable state in the zoonotic pathogen Bartonella henselae induced by low-grade fever temperature and antibiotic treatment - Yuze Gou; Yuze Gou; Dongxia Liu; Dongxia Liu; Yuxian Xin; Yuxian Xin; Ting Wang; Jiaxin Li; Yiwen Xi; Xiaoling Zheng; Tuanjie Che; Ying Zhang; et al. (Frontiers in Cellular and Infection Microbiology)
The zoonotic pathogen Bartonella henselae is responsible for diverse human diseases, from mild to life-threatening, but it often eludes detection in culture-based assays. This study investigates the potential of B. henselae to enter a viable but nonculturable (VBNC) state when exposed to human fever temperature or antibiotics, with this state confirmed by successful resuscitation. Viability was assessed using SYBR Green I/PI staining and propidium monoazide–quantitative polymerase chain reaction (PMA-qPCR), while culturability was determined through colony-forming unit (CFU) counting on blood agar plates. Resuscitation of VBNC cells was attempted using modified Schneider’s medium with 10% defibrillated sheep blood. In the results, B. henselae cells entered a VBNC state after 19 days of exposure to 38.8°C. Antibiotics, particularly with bactericidal activity, induced the VBNC state within 4 days treatment. Successful resuscitation confirmed the VBNC state developed via the above two strategies. Transmission electron microscopy (TEM) examination revealed intact cell structures and dense cytosol in VBNC cells, with a significant increase in plasmolytic cells. Notably, VBNC cells demonstrated greater drug tolerance than cells in the stationary phase, which encompassed a substantial portion of persisters. Proteomic analysis revealed the up-regulation of proteins linked to host cell invasion and stress resistance, while proteins related to signaling and cellular processes were down-regulated. Fluorescence in situ hybridization (FISH) analysis confirmed that the VBNC state truly boosted B. henselae’s invasion of HUVECs. This study highlights B. henselae’s capacity to enter a VBNC state under thermal and antibiotic stress, emphasizing the urgent need for advanced diagnostic and therapeutic strategies to effectively target VBNC cells, which complicate diagnosis and treatment.